DIGITALIZATION OF ZAKAT MANAGEMENT FOR ENHANCED TRANSPARENCY AND POVERTY ALLEVIATION A CASE STUDY OF BAZNAS INDONESIA - Syukrawati Syukrawati; Nadiah Ismail; Chinonso Onyema (Yayasan Adra Karima Hubbi, 2025)
Traditional Zakat management often faces a significant institutional trust deficit, hindering its potential for poverty alleviation. The digitalization of Zakat, as exemplified by Indonesia’s BAZNAS, presents a strategic solution, yet its empirical impact on transparency and social outcomes is under-evaluated. This research aims to empirically evaluate the impact of BAZNAS’s digitalization strategy on enhancing institutional transparency, rebuilding stakeholder trust, and improving the effectiveness of poverty alleviation programs. A mixed-methods explanatory sequential case study of BAZNAS was employed. The study analyzed longitudinal institutional data (2018-2024), structured surveys (n=1000 muzakki and mustahik), and 55 semi-structured stakeholder interviews. Findings reveal a profound positive impact: Zakat collection increased by 153.1% and fund distribution time decreased by 72.3%. ‘Perceived Transparency’ (? = .55, p < .001) was confirmed as the strongest predictor of ‘Institutional Trust’. A statistically significant reduction in mustahik poverty scores was also observed (p < .001). However, a critical ‘Digital Access Gap’ affecting 22% of recipients was identified. Digitalization is empirically validated as a powerful tool for resolving the institutional trust deficit and enhancing Zakat’s effectiveness in poverty reduction. This success is, however, contingent upon developing hybrid strategies to address the digital divide and ensure inclusivity.